Investigating Students' Views on Assessment Models in EFL Classroom - Jhems Richard Hasan; Alvons Habibie (Journal of English Language Teaching, Linguistics, and Literature Studies, 2022)
Investigating Students' Views on Assessment Models in EFL Classroom. One of theimportant elements in the learning context is assessment. This study aimed atexploring the assessment model of teachers used in the teaching and learningprocess in the classroom. The model of assessment measured through students?perception was collected from questionnaire. The survey questionnaire formconsisted of five main components to study students? perception on teachers? stepsin building assessment model. Those are planning of assessment model, presentationof assessment model, various of assessment model in classroom, traditionalassessment model, e-assessment model and disclosure of evaluation results. Basedon the findings of this study, the test model based on students' perceptions eliciteda positive response from English teachers using the model in the classroom.However, it should be noted that the planning for the use of the test model must besubmitted prior to the implementation of the test and comprehensive so thatstudents can prepare themselves adequately for the exam. Furthermore, so thatlearning objectives can be achieved ideally, the use of the test model must also payattention to the level of difficulty and ease of each question item.Keywords: Students? Perception, Assessment Model, EFL Classroom